Randomised controlled trial of adjunctive inspiratory muscle training for patients with COPD. Issue 10 (18th June 2018) - Charususin, Noppawan; Gosselink, Rik; Decramer, Marc; Demeyer, Heleen; McConnell, Alison; Saey, Didier; Maltais, François; Derom, Eric; Vermeersch, Stefanie; Heijdra, Yvonne F; van Helvoort, Hanneke; Garms, Linda; et al.
Abstract : Background: This study aimed to investigate whether adjunctive inspiratory muscle training (IMT) can enhance the well-established benefits of pulmonary rehabilitation (PR) in patients with COPD. Methods: 219 patients with COPD (FEV1 : 42%±16% predicted) with inspiratory muscle weakness (PImax: 51±15 cm H2 O) were randomised into an intervention group (IMT+PR; n=110) or a control group (Sham-IMT+PR; n=109) in this double-blind, multicentre randomised controlled trial between February 2012 and October 2016 (ClinicalTrials.gov NCT01397396 ). Improvement in 6 min walking distance (6MWD) was a priori defined as the primary outcome. Prespecified secondary outcomes included respiratory muscle function and endurance cycling time. Findings: No significant differences between the intervention group (n=89) and the control group (n=85) in improvements in 6MWD were observed (0.3 m, 95% CI −13 to 14, p=0.967). Patients who completed assessments in the intervention group achieved larger gains in inspiratory muscle strength (effect size: 1.07, p<0.001) and endurance (effect size: 0.79, p<0.001) than patients in the control group. 75 s additional improvement in endurance cycling time (95% CI 1 to 149, p=0.048) and significant reductions in Borg dyspnoea score at isotime during the cycling test (95% CI −1.5 to −0.01, p=0.049) were observed in the intervention group. Interpretation: Improvements in respiratory muscle function after adjunctive IMT did not translate into additional improvements in 6MWD (primary outcome). Additional gains in endurance time and reductions in symptoms of dyspnoea were observed during an endurance cycling test (secondary outcome) Trial registration number: NCT01397396 ; Results.